Breaking out of the pandemic: How can firms match internal competence with external resources to shape operational resilience?. Issue 3 (25th April 2022) - Li, Yuan; Wang, Xincheng; Gong, Tianyu; Wang, Haifeng
Abstract: This study explores how firms sought to effectively match their internal competence with external resources from the supply chain network to improve operational resilience (OR) during the COVID‐19 pandemic. Drawing upon matching theory, this study provides an internal–external matching perspective based on flexibility–stability features of OR to explain the operational mechanisms underlying the different matchings between internal flexibility (i.e., product diversity)/stability (i.e., operational efficiency) and external flexibility (i.e., structural holes)/stability (i.e., network centrality). We find that more heterogeneous matchings between internal (external) flexibility and external (internal) stability have a complementary effect that enhances OR, whereas more homogeneous matchings between internal flexibility (or stability) and external flexibility (or stability) have a substitutive effect that reduces OR. This study provides valuable contributions to research focusing on the supply chain, organizational resilience, and operations management. Highlights: Firms need to match their internal competence with supply chain network resources in the correct way to improve their operational resilience in the COVID‐19 pandemic. Matchings between internal flexibility and external stability, and between internal stability and external flexibility can enhance firms' operational resilience in the COVID‐19 pandemic. Firms with high product diversity and occupying the central position in the supply chain network, and with high operational efficiency and more structural holes in the supply chain network can better resist the shock of the COVID‐19 pandemic.